2015
DOI: 10.1111/dote.12442
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal submucosal gland duct adenoma: a clinicopathological and immunohistochemical study with a review of the literature

Abstract: Esophageal submucosal gland duct adenoma (ESGDA) is a rare tumor. The clinicopathological features of the ESGDA and its precursor lesion have not been comprehensively evaluated. In this study, we aimed at delineating the clinicopathological features of the ESGDA and cyst formation of the esophageal submucosal gland duct (ESGD), as well as their correlations and clinical implications. We identified three cases of ESGDA and 16 cases of cyst formation of the ESGD among 786 endoscopic mucosal resection specimens o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Cysts contain mucin and may display papillary intraluminal folds, but lack cytologic atypia. Most examples are encountered among patients with GERD …”
Section: The Submucosal Glands and Their Ducts And The Cardiac Glandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cysts contain mucin and may display papillary intraluminal folds, but lack cytologic atypia. Most examples are encountered among patients with GERD …”
Section: The Submucosal Glands and Their Ducts And The Cardiac Glandsmentioning
confidence: 99%
“…Most examples are encountered among patients with GERD. 77 Glandular elements in the tubular esophagus may give rise to esophageal adenocarcinomas that develop in the upper and mid-esophagus unrelated to columnar-lined esophagus. Nie et al identified three examples of an entity they classified as esophageal submucosal gland duct adenoma.…”
Section: Diseases Of Submucosal Glands and Their Ducts And Cardiac Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The main symptom is abdominal discomfort and dysphagia. They are small hemispherical submucosal lesion that could be removed by endoscopic submucosal dissection (ESD) or endoscopic mucosal resection (EMR) [4]. Although two cases in the literature coexist with carcinoma [5,6], the prognosis of esophageal SGDA itself is favorable.…”
Section: Submucosal Gland Duct Adenomamentioning
confidence: 99%
“…(2) presence of the multilayered epithelium and papillary structures in those glands or cysts, without marked cytologic atypia; (3) lymphocytic aggregation, and atrophy or disappearance of the concomitant acini ( Fig. 2) [4]. The luminal lining cells are positive for MUC5B and various cytokeratins (CKs), including CK5/6, CK7, CK17, CK18, CK19, and HMWCK, while the outer layer cells are positive for p63, and SMA in some cases.…”
Section: Submucosal Gland Duct Adenomamentioning
confidence: 99%